Power of mentorship for civilian and military acute care surgeons: identifying and leveraging opportunities for longitudinal professional development - Brandon Bruns; Jonathan P Meizoso; Lisa Marie Knowlton; Ryan Peter Dumas; Deborah M. Stein; Matthew J Martin; Haytham M A Kaafarani; Nicholas Namias; Kristan L Staudenmayer; William Jason Butler; Brittany K Bankhead; Jan-Michael Van Gent; et al. (Trauma Surgery & Acute Care Open)
Across disciplines, mentorship has been recognized as a key to success. Acute care surgeons, focused on the care of trauma surgery, emergency general surgery and surgical critical care, practice in a wide variety of settings and have unique mentorship needs across all phases of their career. Recognizing the need for robust mentorship and professional development, the American Association for the Surgery of Trauma (AAST) convened an expert panel entitled ‘The Power of Mentorship’ at the 81st annual meeting in September 2022 (Chicago, Illinois). This was a collaboration between the AAST Associate Member Council (consisting of surgical resident, fellow and junior faculty members), the AAST Military Liaison Committee, and the AAST Healthcare Economics Committee. Led by two moderators, the panel consisted of five real-life mentor-mentee pairs. They addressed the following realms of mentorship: clinical, research, executive leadership and career development, mentorship through professional societies, and mentorship for military-trained surgeons. Recommendations, as well as pearls and pitfalls, are summarized below.